EFEK PENGGUNAAN KETAMIN-XILAZIN DAN PROPOFOL TERHADAP DENYUT JANTUNG DAN PERNAFASAN PADA ANJING JANTAN LOKAL (Canis familiaris) (Effect of Ketamine-Xylazine and Propofol on Heart Rate and Breathing Frequency of Local Male Dog (Canis familiaris)) - Arman Sayuti; Ria Maulizar; Syafruddin Syafruddin; Erwin Erwin; Frengky Frengky; Muttaqien Muttaqien; Budianto Panjaitan; Zuraidawati Zuraidawati (Universitas Syiah Kuala, 2016)
The purpose of this study was to determine the effect of using ketamine-xylazin and propofol on heart rate and breathing in local male dogs (Canis familiaris). Six male dogs with average body weight ±2-3 kg were divided into 2 treatment groups, each group was subcutaneously injected with of atropine sulfate at dose of 0.04 mg/kg as premedication prior to anesthetic administration. The first group (K1) was intravenously injected with anesthetic combination of ketamine-xylazine at dose of 5.5 mg/kg and 1 mg/kg, respectively. The second group (K2) was given propofol at dose of 6.6 mg/kg intravenously. The heart rate and breathing were directly calculated using stethoscope and stopwatch with 10 minutes interval. Data were analyzed statistically using analysis of variance (Anova) with split-splot design and if there is a difference between the two groups followed by least significant difference test (LSD). The administration of ketamine-xylazin (K I) significantly (P0.05) increase the respiratory frequency compared to propofol administration (K2). The interaction between time and precise observation of K1 and K2 on 30 minute observation (W3) showed significant differences (P0.05). While on other time observations did not reveal any differences in the interaction between time and observation (P0.05). It can be concluded that there is no difference effects of given ketamine-xylazin and propofol against heart rate on local male dogs. But there was difference effect of administration ketamine-xylazin and propofol on respiratory frequency on local male dogs.